PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN FISIKA KELAS XI PESERTA DIDIK - Rumbino, Ferdinanda; Lumbu, Albert; Lasmono, Paulus G. D. (Universitas Cenderawasih, 2023)
This research has been carried out with the aim of (1) knowing the relationship between learning styles and learning outcomes for physical subjects of students in class IPA2 XI SMA Negeri 1 Sentani, (2) determine the influence of learning styles on learning outcomes of students' physical subjects. IPA2 class XI SMA Negeri 1 Sentani. This research method is quantitative with the presentation of quantitative descriptive data. This research was conducted on students in Class XI SMA Negeri 1 Sentani. The population in this study were students in class XI IPA 2 SMA Negeri 1 Sentani for the academic year 2021/2022 consisting of 252 students consisting of 7 classes. While the sample used in this study was class XI IPA2 students who collected 30 students. This study uses a questionnaire instrument and the Middle Semester Assessment (PTS) of students. The results of the research and data processing show that: (1) There is no relationship between variable (X) and variable (Y) with a significance value of 0.906 > 0.05, which means Ho is accepted and Ha is rejected. (2) There is no effect of variable (X) variable (Y) which shows a significance value of 0.906 > 0.05, which means that there is no effect between variable (X) on variable (Y). This means that Ha is rejected and Ho is accepted